Algal-oil supplements are a viable alternative to fish-oil supplements in terms of docosahexaenoic acid (22:6n-3; DHA). (December 2015) - Ryan, Lisa; Symington, Amy M.
Highlights: Vegetarians and vegans had significantly lower levels of DHA compared with omnivores. Algal-oil significantly improved DHA levels in vegetarians and vegans. DHA from algal oil was accumulated more than DHA from fish oil. Abstract: In an open-label randomized pilot study 31 healthy adults were recruited to consume 600 mg docosahexaenoic acid (DHA)/d sourced from either algal-oil capsules or fish-oil capsules for a period of 2 weeks. The groups were divided into three categories for analysis: omnivore fish-oil (OF) ( n  = 10), omnivore algal-oil (OA) ( n  = 9), and vegetarian/vegan algal-oil (V) ( n  = 12). After the 2-week supplementation period, the % DHA levels increased significantly ( p  < 0.05) in all groups. In terms of bioequivalence, when adjusted for weight, the % change in DHA significantly increased ( p  < 0.05) in group OA compared with group OF. In addition, when comparing all three groups, there was no significant ( p  > 0.05) difference in the final % DHA levels, despite the significantly ( p  < 0.05) lower levels of DHA in the V group at baseline. These results indicate that algal-oil supplements are a sufficient and viable source of DHA for both fish and non-fish eaters alike.